Correlation between quality of life and burden of family caregivers of infants with cleft lip and palate - Marli Luiz Beluci; Cleide Carolina da Silva Demoro Mondini; Armando dos Santos Trettene; Rosana Aparecida Spadoti Dantas (SciELO, 2019)
ABSTRACT Objective: To evaluate the correlation between measures of quality of life and burden in family caregivers of infants with cleft lip and palate and to analyze possible associations between quality of life and sociodemographic variables. Method: Exploratory, cross-sectional study conducted in hospital specialized in the treatment of craniofacial anomalies, with caregivers who answered the following data collection instruments: sociodemographic characterization form, World Health Organization Quality of Life - BREF questionnaire and the Burden Interview Scale. The statistical analysis was conducted using the Pearson's Correlation test, the Student's t-test and the ANOVA test with a level of significance of 0.05. Results: 77 caregivers participated in the study. There was an inverse correlation between quality of life and burden in the Physical Health, Psychological, Social Relationships and Environment domains. There was a positive correlation between quality of life and family income in the Environment domain. Conclusion: The greater the burden on the caregiver, the lower was their perception of quality of life. Caregivers with higher family income and greater level of education presented a better perception quality of life in the Environment domain.